ANALISIS PEMIKIRAN MUSDAH MULIA TENTANG WALI NIKAH DAN RELEVANSINYA TERHADAP PEMBARUAN HUKUM KELUARGA DI INDONESIA - Siti Hafshah Syahanti; Arsal Arsal; Edi Rosman (Institut Agama Islam Negeri (IAIN) Bukittinggi, 2019)
The discussion of marriage guardian is one of the pillars that must exist in a marriage, illegitimate marriage without the presence of a guardian. The Compilation of Islamic Law (KHI) as the law governing Muslim marriages in Indonesia requires guardians as a legal condition of marriage (articles 14 and 19). However, on the other hand, one of the Muslim intellectuals, Siti Musdah Mulia, stated an opposing idea, that guardians are not included in the pillars of marriage. The results showed that the Musdah Mulia thinking generally led to the typology of liberal Islamic thought. Specifically on the issue of the absence of guardians in marriage, Musdah's opinions are not too contrary to the text; Musdah's attention to gender places a substantial portion in establishing the law; and the Musdah idea is not only channeled in the form of thought alone but also poured into the form of a legal regulation draft (CLD-KHI) so that the law applies comprehensively and can be applied clearly and can achieve justice and social benefit in the midst of the people. Then based on this, a specific typology of Musdah Mulia's thought was obtained about the absence of guardians in the marriage harmony leading to progressive Islamic thought. And Musdah Mulia's ideas about the lack of marriage guardians have sufficient relevance to the renewal of Islamic family law in Indonesia.